Melatonina exógena na promoção de tolerância de mudas de Coffea arabica L. ao déficit hídrico - Campos, Cleide Nascimento (2016)
The coffee is very important for the world stage, standing out as the second most traded commodity in the world and fifth most traded agricultural product of the coutry. However cultivation requires coverage of larg áreas, the exposing environmental adversities, of which highlights the growing water scarcity, which constitutes the most limiting environmental factors. So in na attempt to increase the tolerance of plants to diferente environmental stresses, arises interest in the use of substances that promote plant tolerance to biotic and abiotic stresses. Among these molecules melatonina (N-acetyl-5- methoxytryptamine ) stands out, plants whose concentration varies in different tissues and according to the development stage, it is regarded as a promoter of stress tolerance in plants. Thus, the objective this study was to evaluate the effect of exogenous melatonin in inducing tolerance to drought in seedlings Coffea arabica L. the cultivar Catuaí 144. It was observed that melatonin promoted drought tolerance in plants of Coffea arabica L., allowing for better plant growth and reducing oxidative stress caused by water stress condition.